Blood and Hormone Profile of Kacang Goats with a Palisada perforata (Bory) K.W.Nam Supplemented Diet - Nur Hidayah; Cuk Tri Noviandi; Andriyani Astuti; Pradita Iustitia Sitaresmi; Kustantinah Kustantinah (Universitas Sebelas Maret, 2025)
Blood and hormone profile analysis can reliably determine the health status of an animal. This study aimed to test the inclusion of two levels of one red seaweed species, Palisada perforata (Bory) K.W.Nam (PP), at 2.50 to 5.00% organic matter (OM) in a basal diet (total mixed ration/TMR) on the blood (metabolite and hematology) and hormone (glucagon and ghrelin) profiles of Kacang goats. The study employed a randomized complete block design with three treatments and four replicates, involving 12 female Kacang goats with live weights of 23.84±5.26 and 26.96±4.10 kg. The result revealed that for the blood metabolites, supplementation of PP at 2.50% and 5.00% OM (2.97% and 5.94% dry matter, respectively) on the TMR as a basal diet increased (p < 0.05) the glucose and iron concentration, tended to increase (p < 0.1) the total protein, decreased (p < 0.05) the ureum and blood urea nitrogen concentration, and did not affect the cholesterol concentration in the blood of Kacang goats. TMR supplemented with PP at 5.00% OM had the lowest counts (p < 0.01) of white blood cells, lymphocytes, monocytes, and neutrophils. This treatment also increased (p < 0.01) the red blood cells and tended to increase (p < 0.10) the hemoglobin and hematocrit but did not affect the mean corpuscular volume, mean corpuscular hemoglobin, and mean corpuscular hemoglobin concentration of the blood. The plasma glucagon and ghrelin levels decreased (p < 0.01) at 5.00% OM supplementation with this seaweed. Therefore, supplementing a basal diet with PP at 5.00% OM is the optimum treatment to increase the health status of Kacang goats because it exhibits ideal blood and hormone profiles.